Using Pre-emptive Therapeutic Anticoagulation in Moderate to Severe Cases of COVID-19 is Associated with Improved Outcomes - Muhammad Asim Rana, Mujtaba Hasan Siddiqui, Mohammed Rehan Omar Siddiqui, Muhammad Sohail Khalid, Waseem Iqbal, Mohammad Ahad Qayyum, Rizwan Pervaiz, Muhammad Faisal Munir, M. Muneeb Ullah Saif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: There is significant evidence to support that patients with the Coronavirus disease 2019 (COVID-19) have a higher propensity to develop thrombotic events. COVID-19 patients in intensive care units (ICU) have an increased rate of venous thromboembolism (VTE), ranging from 17% to 25%. Apart from acute respiratory failure, coagulopathy remains a common abnormality in these patients, within creased levels of both fibrinogen and D-dimers. Anticoagulation using subcutaneous heparin is known to reduce the incidence of thromboembolic events; although concern regarding over-anticoagulation resulting in excessive bleeding remains an impediment. Objective: Study Design: Retrospective study Place and Duration of Study: Bahria International Hospital Lahore from 1st May 2020 to 31st October 2020. Methodology: One hundred and eight patients admitted in the ICU were enrolled. The incidence of thrombotic and bleeding events in patients treated with subcutaneous heparin during their admission with moderate to severe COVID19 in the ICU. All patients were given therapeutic dosed anticoagulation universally unless contraindicated. Results: Thromboembolic events were seen in 10 patients while 98 patients did not have any such event. 3 patients had a bleeding event during their stay. Conclusions: Using prophylactic therapeutic dose anti-coagulation therapy is an effective and safe strategy in COVID-19 patients and it is associated with improved outcomes in terms of reducing morbidity and mortality.